Recent improvements in photometric stereo for rock art 3D imaging. Issue 2 (2015) - Dessì, R.; Mannu, C.; Rodriguez, G.; Tanda, G.; Vanzi, M.
Abstract: Recent improvements in photometric stereo (PS) are shown to remove the major limitations of this low-cost 3D recording technique. In particular, there are significant improvements in lighting constraints, processing time and presence of deformation in reconstructed surfaces, allowing for fast and accurate restoration of shape and color information. The shooting technique is sufficiently easy to make PS ideal for ancient rock art, which is generally encountered in difficult to access sites, where many of the rock engravings to survey are often placed in a narrow space. This paper focuses on the Sardinia neolithic tombs known as Domus de Janas, as they offer an opportunity to demonstrate the applicability of PS to general rock art.